From the Classroom to the Keyboard: How Seven Teachers Created Their Online Teacher Identities - Richardson, Jennifer C.; Alsup, Janet (International Review of Research in Open and Distributed Learning, 2015)
Teacher identity is defined as a sense of teacher self that results from a productive combination of key personal and professional subjectivities or beliefs. Much empirical research has been done on the development of teacher identity in the K-12 arena, with a great deal of theoretical and philosophical scholarship about teaching at the college level, yet little research to date has looked at how instructors at the college level, especially those who are teaching online, develop their online instructor identity. The purpose of this interview-based, qualitative study is to understand the experience of first time online instructors and how they develop their online teacher identity and utilizes the framework established by Beijaard, Meijer and Verloop (2004) as the lens for analyses. Recommendations are made for cultivating online teacher identity and the many aspects of it as a means to strengthen online teacher identity to not only provide effective and innovative teaching experiences but also for the sake of retention.